Pendidikan Karakter Pada Anak Sekolah Dasar Di Era Digital - Putri, Dini Palupi (AR-RIAYAH : Jurnal Pendidikan Dasar, 2018)
Character education is an application process of etiquette value and religious into the students through knowledge, the application of the values to yourself, family and each friends into the teacher, environment and also into God Almighty. The social development of the child in the age of the elementary school have increase. From the first only socialize with the family in the house and then grow up to know another people around him. The child in this age also know the digital style either in the house, friends, school and the environment. In the digital era itâs not only positive impact but also negative impact. In this case the figure of the parents, teacher and society are working to guide and watch the child to become good, excellent and have the positive aim to their self